Resilient Strategy of the Successful Business in the Community for Gen Y Entrepreneurs towards the New Normal in Chiang Mai Province - Phungphol, Wilai (Business Administration and Management Journal Review, 2022)
This research focuses on the resilient business strategy in the community of gen Y entrepreneurs in Chiang Mai province. The qualitative method was sought for 23 key informants and used a template analysis approach and an inductive approach for data collection. The results of the presentation of the resilient strategy in a holistic dimension include a proactive family concept, the design way on an intelligent logistic system to deliver to customers on time hygienically, the self-care for both physical and mental health, continuous Learning and development, and the adaptation of thinking to support public applications for expenditure from the population. The final turnaround strategy in action was to prepare the production of quality products to be new, set a value price for the customers’ needs and good service, build an honest network of contemporary culture preservation online for creating a positive customer experience, hear the customers’ voice, group customers for thorough care, and be a good consultant. The additional results found a careful turnaround, word-of-mouth resurgence in gen Z viral marketing, and exceeding services expectations in a new normal.